Konsentrasi Hambat Minimum dan Konsentrasi Bunuh Minimum Ekstrak Dan Nanopartikel Ekstrak Daun Pometia pinnata Terhadap Staphyloccocus aureus dan Escherichia coli - Sony , Suyefri; Rahayu, Yayuk Putri; Nasution , Haris Munandar; Rani, Zulmai (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Infectious diseases caused by bacteria such as Escherichia coli and Staphylococcus aureus have become a global health issue. Matoa leaves (Pometia pinnata) are known to contain antibacterial compounds that hold potential as alternative treatments. Objective: This study aimed to produce nanoparticles from the ethanol extract of matoa leaves and compare the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values of both the extract and its nanoparticles against Escherichia coli and Staphylococcus aureus. Methods: This experimental research used different concentrations of matoa leaf ethanol extract (6.25%, 12.5%, 25%, 50%) and nanoparticle extract (0.625%, 1.25%, 2.5%, 5%). Nanoparticle characterization was performed using a Particle Size Analyzer (PSA). Results: The nanoparticle characterization showed a size of 528.95 nm. The MIC value of the matoa leaf extract against Escherichia coli and Staphylococcus aureus was 12.5%, while for the nanoparticles, it was 1.25%. The MBC value of the matoa leaf extract was 50%, and for the nanoparticles, it was 5%. The highest antibacterial activity of the ethanol extract was 18.3 mm and 18.4 mm, while for the nanoparticles, it was 18.5 mm and 19.0 mm. Conclusion: The nanoparticle extract of matoa leaves was more effective in inhibiting and killing bacteria compared to the regular extract, with a lower dose (1:10), showing its potential as an efficient antibacterial alternative.